Prevalensi Multidrug-Resistant Klebsiella pneumonia dan Evaluasi Kesesuaian Antibiotik Empiris Berdasarkan Nilai Prediksi Farmakokinetik Terhadap Outcome Klinis di RSUP Dr Soeradji Tirtonegoro Klaten - Rizqi Nurul Khasanah; Ika Puspitasari; Titik Nuryastuti; Nunung Yuniarti (Majalah Farmaseutik, 2020)
Klebsiella pneumonia is a multidrug resistant (MDR) pathogen that affects morbidity and mortality. MDR K. pneumonia is the bacterium K. pneumonia which has experienced resistance to at least one antibiotic from 3 or more antibiotic groups. The purpose of this study was to see the percentage prevalence of MDR K. pneumonia events and to see profiles of antibiotic sensitivity and predictions of antibiotic pharmacokinetic parameters in hospitalized patients at RSUP dr. Soeradji Tirtonegoro Klaten from 2017 to 2018. This study was an observational study with a cross sectional method and retrospective data collection. Data collected included the number of inpatients who experienced MDR K. pneumonia and the factors that influence the occurrence of antibiotic resistance. The prevalence of MDR K. pneumonia and antibiotic sensitivity evaluation were analyzed descriptively. Prediction of antibiotic pharmacokinetics in patients with MDR K. pneumonia associated with patient clinical outcomes was analyzed in Chi-square. Patients infected with Klebsiella pneumonia as many as 338 patients found 67 patients with MDR K. pneumonia who met the inclusion criteria in hospitalized patients at RSUP dr. Soeradji Tirtonegoro Klaten. The prevalence of MDR K. pneumonia in 2017-2018 is 30.17%. The results of the analysis show that there is a relationship between empirical antibiotic suitability based on pharmacokinetic predictiion value to clinical outcomes with a probability value of P = 0.024 (P <0.05).